The dominance of the consumption pattern of government Expenditure and its impact on economic growth of Iraq for the period 2003-2014 - داود, سمير سهام; لطيف, مقداد غضبان (Journal of Economics and Administrative Sciences, 2017)
The importance of government Expenditure policy in economy come from its role leading to the mitigation and adjustment of fluctuations in macroeconomic variables caused by imbalance between aggregate demand and aggregate supply,  It is associated with the efficient management of government Expenditure to reinforcement the relationship between government Expenditure and the overall economic system .Regarding the Iraqi economy,the increasing in financial rentier after the political change in 2003 has led to finance the budgets Characterized by consumption,The government Expenditure employed to encourage government employment in services jobs, and find different channels for the distribution of oil rent expands with height of the oil revenues, versus failing in  formation  infrastructure stimulate growth in economy, resulting in generation a huge demand,to be meet that demand through the trade. The dominance of consumption Expenditure on government Expenditure and its association with rent oil has made government Expenditure lacks a lot of ways to direct the real variables of economic in the desired shape ,as long as the structural imbalance remained rooted in the structure of the economy, these trends have made policy of Expenditure suffering contradiction, the Expenditure policy couldnot unification its ways to achieving the target of production efficiency and fairness of the distribution of rent , and expanding consumption in the economy boosted not absorbed by local supply  because of continuation of the private sector Carries on service and commercial activities intrude on oil revenues without access productive activities to cover the growing gap between aggregate demand and aggregate supply and investment this gap as areal incentives to increase  production according to profitability criteria to be objective conditions for sustainable economic growth